IMPROVING STUDENTS’ SCIENCE LITERACY COMPETENCIES ON EARTH AND ITS SATELLITES THROUGH STRUCTURED INQUIRY LEARNING - Sarah, Annisa Rosita; Astriani, Dyah (PENSA E-JURNAL: PENDIDIKAN SAINS, 2024)
This research aims to describe the improvement of students’ science literacy competencies through structured inquiry learning on Earth and its satellites material. The subjects used in this study were students in the VII-C grade at Sidoarjo Junior High School. This research used a pre-experimental with one group pre-test-post-test design. This research used science literacy test sheets to collect data by pre-test (before treatment) and post-test (after treatment). The data obtained were analyzed to decide whether or not there was a student’s science literacy improvement after being given learning with the structured inquiry model. The analysis results of the improvement of students’ science literacy competencies with a gain score of 0.68 in the medium category, the results of the pre-test and post-test scores different significant with sig. (2-tailed) of 0.000, the achievement of science literacy competency indicators had increased with a medium category in indicator 1 and a high category in indicators 2 and 3.